Exercise-based cardio-oncology rehabilitation for cardiotoxicity prevention during breast cancer chemotherapy: The ONCORE randomized controlled trial - Díaz-Balboa, Estibaliz; Peña-Gil, Carlos; Rodríguez-Romero, Beatriz; Cuesta-Vargas, Antonio; Lado-Baleato, Oscar; Martínez-Monzonís, Amparo; Pedreira-Pérez, Milagros; Palacios-Ozores, Patricia; López-López, Rafael; González-Juanatey, José R.; González-Salvado, Violeta (Elsevier, 2024)
Background: Breast cancer (BC) treatment with anthracyclines and/or anti-human epidermal growth factor receptor-2 (HER2) antibodies is associated with an increased risk of cardiovascular disease complications, including cancer therapy-related cardiac dysfunction (CTRCD). While Cardio-Oncology Rehabilitation (CORe) programs including exercise have emerged to minimize these risks, its role in preventing CTRCD is unclear. Objectives: We investigated the effectiveness of an exercise-based CORe program in preventing CTRCD [left ventricular ejection fraction (LVEF) drop ≥10% to a value <53% or a decrease >15% in global longitudinal strain (GLS)]. Secondary outcomes examined changes in cardiac biomarkers, physical performance including peak oxygen consumption, psychometric and lifestyle outcomes. Safety, adherence, and patient satisfaction were also assessed. Methods: This is a randomized controlled trial including 122 early-stage BC women receiving anthracyclines and/or anti-HER2 antibodies, randomized to CORe (n = 60) or usual care with exercise recommendation (n = 62). Comprehensive assessments were performed at baseline and after cardiotoxic treatment completion. The average duration of the intervention was 5.8 months. Results: No cases of CTRCD were identified during the study. LVEF decreased in both groups, but was significantly attenuated in the CORe group [-1.5% (-2.9, -0.1); p = 0.006], with no changes detected in GLS or cardiac biomarkers. The CORe intervention led to significant body mass index (BMI) reduction (p = 0.037), especially in obese patients [3.1 kg/m2 (1.3, 4.8)]. Physical performance and quality-of-life remained stable, while physical activity level increased in both groups. No adverse events were detected. Conclusions: This study suggests that CORe programs are safe and may help attenuate LVEF decline in BC women receiving cardiotoxic therapy and reduce BMI in obese patients.
Keywords: Mamas - Cáncer; Ejercicio físico - Uso terapéutico; Breast cancer; Cardio-oncology rehabilitation; Cardiotoxicity; Cardiovascular prevention; Exercise